2019
DOI: 10.1039/c8qo01249k
|View full text |Cite
|
Sign up to set email alerts
|

Trifluoromethyl-substituted selenium ylide: a broadly applicable electrophilic trifluoromethylating reagent

Abstract: An easily available, air/moisture insensitive and broadly applicable electrophilic reagent trifluoromethyl-substituted selenium ylide 1a and its reactions with a variety of nucleophiles including β-ketoesters and silyl enol ethers, aryl/heteroaryl boronic acids, electron-rich heteroarenes and sulfinates were described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 46 publications
1
35
0
Order By: Relevance
“…Similar patterns are noted in 164 [208] , Fig. 16 c, and 165 [209] but, with the bridges leading to the chains being interactions of the type Se … O(nitro); in 164 , the Se … O(carbonyl) separations are shorter than the Se … O(nitro) contacts whereas the opposite trend pertains in 165 , underscoring the difficulty of correlating distances associated with weak interactions as discussed in section 8. In 166 [210] , Fig.…”
Section: One-dimensional Assembles Mediated By Se … supporting
confidence: 62%
See 1 more Smart Citation
“…Similar patterns are noted in 164 [208] , Fig. 16 c, and 165 [209] but, with the bridges leading to the chains being interactions of the type Se … O(nitro); in 164 , the Se … O(carbonyl) separations are shorter than the Se … O(nitro) contacts whereas the opposite trend pertains in 165 , underscoring the difficulty of correlating distances associated with weak interactions as discussed in section 8. In 166 [210] , Fig.…”
Section: One-dimensional Assembles Mediated By Se … supporting
confidence: 62%
“…The chemical diagrams for these species, i.e. 160 – 180 [93] , [104] , [105] , [113] , [188] , [206] , [207] , [208] , [209] , [210] , [211] , [212] , [213] , [214] , [215] , [216] , [217] , are shown in Fig. 15 .…”
Section: One-dimensional Assembles Mediated By Se … mentioning
confidence: 99%
“…The reaction proceeded through a direct nucleophilic addition of diazo compounds to difluorocarbene followed by elimination of N 2 , and furnished a variety of 1,1difluoroalkenes (34 and 37), e. g., difluoroacrylates, diaryldifluoroolefins, and arylalkyldifluoroolefins, which showed a broader 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 substrate scope than that of the Cu-catalyzed difluoroolefination. [14] Diazirines (39) were used as the surrogates of the less stable arylalkyldiazomethanes (40) in the reaction, which could selectively form the corresponding 1,1difluoroalkenes (41) or the cyclopropanation products (42) by changing the ratios of 39 to TMSCF 2 Br. Two possible reaction pathways might be involved in this difluoroolefination (Scheme 5), and the direct carbene-carbene cross-coupling is probably less rational (path b) according to the control experiments.…”
Section: Gem-difluoroolefination and The Related Transformationmentioning
confidence: 99%
“…This reaction provided another useful approach for the synthesis of α-trifluoromethylselenolated esters, showing good compatibility with a wide range of functional groups, like methoxy, methylmercapto, fluoro, chloro, Recently, Shen and Zhang separately announced the preparation of trifluoromethyl aryl selenium ylides (166) by reactions of aryl trifluoromethyl selenoethers (164) with diazomalonates (165) in the presence of 0.1 mol% Rh 2 (esp) 2 at 40°C, which is regarded as an expanded contribution of trifluoromethylselenolation of α-diazo esters (Scheme 27). [40,41] Shen and coworkers found that 4-nitrophenyl trifluoromethyl selenium ylide (166 a) was a highly reactive electrophilic trifluoromethylation reagent which could efficiently trifluoromethylate a variety of nucleophiles, including βketoesters, silyl enol ethers, aryl/heteroaryl boronic acids, electron-rich heteroarenes, and sulfinates, with bases, copper catalysts and/or visible light irradiation under mild conditions (Scheme 27). [40] Shortly after, Zhang and coworkers uncovered that when trifluoromethyl aryl selenium ylides (166) reacted with aryl halides (177) in the presence of a copper catalyst, diaryl selenides (178) rather than trifluoromethylated products were obtained in good to high yields in the reaction (Scheme 27).…”
Section: Trifluoromethylselenolationmentioning
confidence: 99%
See 1 more Smart Citation